2010
DOI: 10.2337/dc09-1810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment of Gestational Diabetes Mellitus on Obesity in the Next Generation

Abstract: OBJECTIVEGestational diabetes mellitus (GDM) may cause obesity in the offspring. The objective was to assess the effect of treatment for mild GDM on the BMI of 4- to 5-year-old children.RESEARCH DESIGN AND METHODSParticipants were 199 mothers who participated in a randomized controlled trial of the treatment of mild GDM during pregnancy and their children. Trained nurses measured the height and weight of the children at preschool visits in a state-wide surveillance program in the state of South Australia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(183 citation statements)
references
References 15 publications
7
172
2
2
Order By: Relevance
“…31 Yet, with some exceptions, there are few early life cycle studies that aim to address early childhood obesity by intervening during the prenatal phases of development. 32 Observational studies that follow children born of mothers who were participants in lifestyle interventions targeting gestational weight gain or gestational diabetes have not found a ''spillover'' effect on childhood obesity or metabolic profile. [32][33][34] Grounding interventions in life course theoretical models and developing solution-focused intervention strategies that cover both prenatal and early postnatal behavioral changes may be needed to advance the evidence base in this area.…”
Section: Discussionmentioning
confidence: 99%
“…31 Yet, with some exceptions, there are few early life cycle studies that aim to address early childhood obesity by intervening during the prenatal phases of development. 32 Observational studies that follow children born of mothers who were participants in lifestyle interventions targeting gestational weight gain or gestational diabetes have not found a ''spillover'' effect on childhood obesity or metabolic profile. [32][33][34] Grounding interventions in life course theoretical models and developing solution-focused intervention strategies that cover both prenatal and early postnatal behavioral changes may be needed to advance the evidence base in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a real outcome might be less than optimal outcome we might want, that is some of the children from mothers who implement the lifestyle recommendation would be overweight or obese and having hypertension at the age of 10. The results of an RCT targeting women with mild GDM between 24-34 weeks gestation with predominantly dietary interventions and blood glucose monitoring fail to show significant difference in BMI of the children at age 4 to 5 years old 10 . Upon this null effect size, the author argues that they can not adjust the results for possibility the effect of post natal factor that determine the height and weight of the child for example the food eaten and physical exercise, overpower the effect of treating GDM during pregnancy 10 .…”
Section: Iugrmentioning
confidence: 99%
“…The results of an RCT targeting women with mild GDM between 24-34 weeks gestation with predominantly dietary interventions and blood glucose monitoring fail to show significant difference in BMI of the children at age 4 to 5 years old 10 . Upon this null effect size, the author argues that they can not adjust the results for possibility the effect of post natal factor that determine the height and weight of the child for example the food eaten and physical exercise, overpower the effect of treating GDM during pregnancy 10 . Furthermore the authors argue that the effect of fetal origin of disease might be takes more time to occurs by citing the finding from Pima Indian study that showed association of maternal GDM with the offspring BMI after the age of 9, but not before 10 .…”
Section: Iugrmentioning
confidence: 99%
See 2 more Smart Citations